(untitled) (Fiep Bulletin - online, 2011)
Introduction: The aging can be conceptualized as a dynamic and progressive process where there is both morphological changes such as functional, biochemical and psychological loss that determine the adaptability of the individual. Objective: To evaluate the strength and endurance of lower limbs and quality of life for seniors through the test "30-sec Chair Stand test (sitting and rising from a chair in 30 seconds). Methodology: descriptive study, conducted in institutionalized elderly. Inclusion criteria: independence for ambulation and acceptance to participate. Results: 12 elderly people participated (10 women and 2 men), and most have 84 years of age (18% of the sample), who obtained a result of weakness in the legs. Conclusion: we conclude that it is possible to identify future problems in a matter of strength and endurance of lower limbs in institutionalized elderly.